2022
DOI: 10.1111/jop.13318
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathways and possible therapies for head and neck vascular anomalies

Abstract: Vascular anomalies are a heterogenous group of vascular lesions that can be divided, according to the International Society for the Study of Vascular Anomalies Classification, into two main groups: vascular tumors and vascular malformations. Vascular malformations can be further subdivided into slow-flow and fast-flow malformations. This clinical and radiological classification allows for a better understanding of vascular anomalies and aims to offer a more precise final diagnosis. Correct diagnosis is essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…The development of OSCC is often related to change in molecular level of the receptor tyrosine kinase (RTK), PI3K/AKT, and p53 pathway, and G1/S cell cycle transition [ 31 - 33 ]. The PI3K family kinases are lipid kinases comprising of the catalytic subunits (p110α, p110β, p110δ and regulatory subunits (p85α, p85β, p55γ, p55α, p50α) and are downstream of RTKs.…”
Section: Discussionmentioning
confidence: 99%
“…The development of OSCC is often related to change in molecular level of the receptor tyrosine kinase (RTK), PI3K/AKT, and p53 pathway, and G1/S cell cycle transition [ 31 - 33 ]. The PI3K family kinases are lipid kinases comprising of the catalytic subunits (p110α, p110β, p110δ and regulatory subunits (p85α, p85β, p55γ, p55α, p50α) and are downstream of RTKs.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of somatic mutations in vascular anomalies offers an opportunity to uncover disease-causing pathways and develop new targeted therapies, which will require preclinical cell and animal models carrying these mutations. 25,26 KLA patients often have the NRAS Q61R mutation in lesion tissue 27 and elevated blood Ang-2 levels. 18,19 However, whether these are directly related was unclear, as these patients have a complex pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Additionally, partial somatic mutations and abnormal signaling pathways that can potentially induce endothelial cell dysfunction have been observed in sporadic AVMs. 6 Researchers have suggested that MAP2K1 gene mutations may be related to sporadic AVM onset, 1 along with the implication of RASA1 , EPHB4 , ENG , BMP9 , ACVRL1 , SMAD4 , and BMPR2 gene mutations in AVM-related disorders. 5 Moreover, researchers investigating the molecular mechanisms of AVMs have proposed rapamycin or trimetinib as potential target drugs to treat AVMs 7 , 8 ; however, more investigations are required to support this strategy.…”
Section: Etiologymentioning
confidence: 99%